ELECTRONIC ANALYSIS OF WORD OF MOUTH, PRICE, AND PROMOTION TO DECISIONS USE OF GOJEK TRANSPORTATION SERVICES IN CENTRAL CIKARANG SUBDISTRICT - Asral Asral; Ardina Hendriani (SEAN Institute, 2022)
The advancement of digital technology in the marketing world is growing quite rapidly. Where everyone can access anything at hand via a smartphone. A new innovation in the transportation sector is application-based transportation or it can also be called online transportation services. In this case, to support a decision to use, it is followed by the influence of electronic word of mouth, prices, and good promotions to attract consumers.This study aims to analyze the effect of Electronic word of mouth, price, and promotion on the decision to use Gojek in Central Cikarang District, both partially and simultaneously. The data collection technique used purposive sampling technique with a sample of 100 respondents. This study uses quantitative methods using validity tests, reliability tests, multiple regression analysis, autocorrelation test, coefficient of determination (R2) test, t test and F test. Based on test results using t test shows Electronic word of mouth, price, and promotion partially and simultaneous positive and significant effect on the decision to use and the results of testing the coefficient of determination on Adjusted R Square all variables are able to explain the effect of Electronic word of mouth, price, and promotion on the decision to use by 40.9% while 59.1% is influenced by other factors.